2014
DOI: 10.1021/jf503681r
|View full text |Cite
|
Sign up to set email alerts
|

Carrot Juice Fermented with Lactobacillus plantarum NCU116 Ameliorates Type 2 Diabetes in Rats

Abstract: The effect of carrot juice fermented with Lactobacillus plantarum NCU116 on high-fat and low-dose streptozotocin (STZ)-induced type 2 diabetes in rats was studied. Rats were randomly divided into five groups: non-diabetes mellitus (NDM), untreated diabetes mellitus (DM), DM plus L. plantarum NCU116 (NCU), DM plus fermented carrot juice with L. plantarum NCU116 (FCJ), and DM plus non-fermented carrot juice (NFCJ). Treatments of NCU and FCJ for 5 weeks were found to favorably regulate blood glucose, hormones, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 41 publications
3
81
0
1
Order By: Relevance
“…Type 2 DM (T2DM) constitutes a large proportion of cases of DM, and recently its incidence has rapidly increased worldwide (Li et al . ). Thus, primary prevention and effective treatment in the general population is the ultimate goal.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 DM (T2DM) constitutes a large proportion of cases of DM, and recently its incidence has rapidly increased worldwide (Li et al . ). Thus, primary prevention and effective treatment in the general population is the ultimate goal.…”
Section: Introductionmentioning
confidence: 99%
“…As fermented juice with probiotics has been shown to exhibit nutritional and health-promoting effects (Marazza, LeBlanc, Giori, & Garro, 2013), it is necessary to elucidate the mechanism of those beneficial effects. Some studies have demonstrated that the hypocholesterolemic and hypolipidemic effects of fermented fruit and/or vegetable juices (Jeon, Kim, Mun, Cha, & Yu, 2017;Li et al, 2014) might be associated with the organic acids (Parvez et al, 2006) and short-chain fatty acids (Li et al, 2014) produced by LAB or with thepolyphenolic compounds derived from juice materials (Hertog et al, 1993;Yugarani, Tan, & T, M., & Das, N. P., 1992) that have antiatherogenic activity.…”
Section: Cholesterol-lowering Effects Of Em Juice In Rats Fed a Higmentioning
confidence: 99%
“…• microbiota-based bile acid-chloride exchange mechanism: decrease in the number of bile acid 7α-dehydroxylating activity possessing bacteria, bile acid elimination, upregulating of chloride ion-dependent genes (ClC1-7, GlyRa1, SLC26A3, SLC26A6, GABAAa1, bestrophin-3 and CFTR) and prevention of chloride ion loss Li et al 23 Experimental study.…”
Section: Lactobacillus Caseimentioning
confidence: 99%
“…23 Another study 26 indicated that administration of Lactobacillus plantarum No. 14 prevents development of insulin resistance, mainly through reducing accumulations of visceral fat, which prevents production of pro-inflammatory adipokines.…”
Section: Also Administration Of Lactobacillus Kefiranofaciens M Andmentioning
confidence: 99%
See 1 more Smart Citation